Effect Of The Combination Of Aloe Vera And Palm Sugar On The Improvement Of Diabetic Ulcers In Patients With Type 2 Diabetes Mellitus - Devi Ratnasari; Zahara Farhan; Dani Sujana; Kurniawan Dewi Budiarti (Jurnal sosial dan sains, 2022)
Background: Diabetic ulcer treatment with aloe vera and palm sugar is one of the treatment measures to prevent infection in diabetic ulcers. Aloe vera contains auxin, gibber-relin, anthraquinone, and vitamins A, C, and E as an anti-inflammatory, antipyretic, antioxidant, antiseptic, antimicrobial, as well as antiviral.  Aloe vera can diffuse properly and can withstand the loss of body fluids from the surface of the skin so that moisture is maintained, while palm sugar contains vitamin C, Riboflavin, vitamin A, and ascorbic acid as antibiotics and improves the tissue work system which can weaken and kill bacteria that cause infections in diabetic ulcers. Purpose: The purpose of this study was to determine the effect of the combination of aloe vera and palm sugar on the improvement of diabetic ulcers in patients with type 2 diabetes mellitus. Method: One group pretest and posttest design research design in one subject group with a total sample of 8 people, sampling technique using consecutive sampling, the research was carried out in August 2022 at the Wanaraja health center, Garut Regency Results:  Based on the results of the study, it is known that the highest activity that occurs in Macaca fascicularis at Sangeh Tourism Object is in the behavior of moves (moving) with a percentage of 17%, and Grooming behavior (Looking for lice) by 15%, then for other activities such as rest (rest) by 14  %, mating 8%, feeding 13%, social 14%, agonistic 13%, for behavior with the lowest percentage of sleep (sleep) of 6%. Conclusion: Conclusion of the study, the combination of aloe vera and palm sugar affects the improvement of diabetic ulcers in patients with type 2 diabetes mellitus